2000
DOI: 10.1159/000041048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the C677T Methylenetetra- hydrofolate Reductase Mutation in Thai Patients with Deep Vein Thrombosis

Abstract: We investigated the prevalence of a genetic variation in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene (C677T) using polymerase chain reaction techniques in a sample of 500 general Thai population and among 40 unselected Thai patients with an objectively confirmed history of deep vein thrombosis (DVT). The prevalence of the mutated homozygous and heterozygous C677T MTHFR genotype in the group of 500 healthy Thai population was 1.4 and 25.6%, respectively (allele frequency of 14.2%). Of the 40 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The frequency of the 677T allele in our controls was 12%, which is comparable to the frequencies of 14% in the control population reported in independent studies in Thailand. 23 Our results agree with a previous observation that the polymorphism was found in every population tested and its frequency among Asians is quite similar to that of Europeans, but higher than in Africans. 24 The frequency of the 1298C allele in our controls was 27%, which is similar to that of white populations (27-33%).…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of the 677T allele in our controls was 12%, which is comparable to the frequencies of 14% in the control population reported in independent studies in Thailand. 23 Our results agree with a previous observation that the polymorphism was found in every population tested and its frequency among Asians is quite similar to that of Europeans, but higher than in Africans. 24 The frequency of the 1298C allele in our controls was 27%, which is similar to that of white populations (27-33%).…”
Section: Discussionsupporting
confidence: 92%
“…[6][7][8] Other studies from Thailand demonstrated a lower incidence of mutations in genes which predispose to thrombosis such as factor V leiden, prothrombin 20210 and methylenetetrahydrofolate reductase (MTHFR) C677T. [9][10][11] These results correspond with reports from other Asian countries. [12][13][14][15][16] Other than genetic polymorphism, the difference in fibrinolytic activity, 17 lifestyle factors, the prevalence of obesity as well as psychosocial stress also affect the incidence of thromboembolism.…”
supporting
confidence: 68%
“…39 The most common hereditary risk factors associated with ischemic stroke were identified as factor V leiden mutation, an increased level of lipoprotein a, protein C deficiency, and/ or the presence of antiphospholipid antibody. 39 Because studies have shown that factor V leiden mutation seems to be lower among Thai and other Asian populations, 9,10 it is therefore hypothesized that risk factors for thromboembolism might also differ between different regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] According to Fowler, 31 the frequency of homozygous variant of MTHFR gene was present in 5-18% of population. Our meta-analysis suggests that frequency distribution of homozygous TT genotype was present in 23.5% in Asian and 12.8% in Caucasian population.…”
Section: Discussionmentioning
confidence: 99%